Characterization and formation of σ/γ interface in Ni-based single crystal superalloys. (15th November 2017) - Ma, Shiyu; Zhang, Jianxin; Li, Xueqiao; Mao, Shengcheng
Abstract: High-resolution transmission electron microscopy was used to study interfacial characteristics between the plate-shaped σ phase and the γ phase in a Ni-based single crystal superalloy. The atomic structure of the σ / γ interface constituted by steps was presented. However, the HRTEM micrograph of σ phase is not almost identical with the veritable atomic arrangement of σ phase on the same zone axis. The image formation of HRTEM relies on phase contrast, instead of the amplification of the atomic arrangement. From the simulated HRTEM images, the approximate defocus and thickness of the sample can be got as −3 nm and 6 nm. σ phase has the following crystallographic orientations relations with γ matrix: [0 0 1] γ //[1 1 2] σ, (1 1 0) γ //(1 −1 0) σ, (−1 1 0) γ //(1 1 −1) σ, which can be proved by the stereographic projection. The interfacial steps are made up by (1 1 0) γ and (−1 1 0) γ or (1 −1 0) σ and (1 1 −1) σ . In the interface steps, the length of (−1 1 0) γ //(1 1 −1) σ is longer than (1 1 0) γ //(1 −1 0) σ, which is caused by that distortion factor of (−1 1 0) γ //(1 1 −1) σ is much smaller than that of (1 1 0) γ //(1 −1 0) σ .